Study of clinical and epidemiological profile of poisonous snake bite in a tertiary centre in North Kerala - Mathews, Manu; Balakrishnan, Sudha (International Journal of Research in Medical Sciences, 2019)
Background: Snakebites are well-known medical emergencies in many parts of the world, especially in rural areas. The incidence of snakebite mortality is particularly high in South-East Asia. Rational use of snake anti-venom can substantially reduce mortality and morbidity due to snakebites. Snake bite is an important health problem in India also especially in North Kerala which has an agricultural background. There is a lack of study regarding this topic in this area. North Kerala differs from other areas in the country as hump nosed pit viper bites are more common here due to its proximity to western Ghats where it .Anti snake venom is ineffective to bites by hump nosed pit viper. Authors objectives was to assess the clinical and epidemiological profile and outcome of poisonous snake bites. Methods: Retrospective observational study done among patients with snake bite with envenomation admitted in Academy of Medical education, Pariyaram, Kannur, Kerala from January 2018 to September 2018. Results: There were 90 cases of venomous snake bite during the study period. Of these males were predominant (70%). Majority were in the age group between 20 and 40. Majority of bites occurred in the months of June and July. Bite in the extremities were more common. Nine patients were brought 1 day after the bite. Snake identified most common was Russell’s viper followed by pit viper. Majority of the systemic envenomation was hemotoxic 80 patients (85%). Conclusions: The study stress the fact that snake bite is an important problem in North Kerala. The study also shows that delay in treatment is a major risk factor for morbidity. Hump nosed pit viper bites are more common in this area.